2015
DOI: 10.1186/s13323-015-0031-1
|View full text |Cite
|
Sign up to set email alerts
|

Tracing Jomon and Yayoi ancestries in Japan using ALDH2 and JC virus genotype distributions

Abstract: BackgroundAccording to the dual structure model, the modern Japanese ethnic population consists of a mixture of the Jomon people, who have existed in Japan since at least the New Stone Age, and the Yayoi people, who migrated to western Japan from China around the year 300 bc Some reports show that the Yayoi are linked to a mutation of the aldehyde dehydrogenase 2 gene (ALDH2).Recent viral studies indicate two major groups found in the Japanese population: a group with the CY genotype JC virus (JCV) and a group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…We previously analyzed the relationship between JCV genotype and ALDH2 genotype in people who live in mainland Japan. We found that people who carry CY genotype JCV have a higher frequency of ALDH2 mutation than that of people who carry MY genotype JCV (P < 0.05) 16 . This result suggested that the Jomon people initially carried MY genotype JCV and wild-type ALDH2 in the Japanese archipelago and, subsequently, Yayoi people who carried CY genotype JCV and a variant of ALDH2 migrated from the Chinese continent throughout the Korean peninsula.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…We previously analyzed the relationship between JCV genotype and ALDH2 genotype in people who live in mainland Japan. We found that people who carry CY genotype JCV have a higher frequency of ALDH2 mutation than that of people who carry MY genotype JCV (P < 0.05) 16 . This result suggested that the Jomon people initially carried MY genotype JCV and wild-type ALDH2 in the Japanese archipelago and, subsequently, Yayoi people who carried CY genotype JCV and a variant of ALDH2 migrated from the Chinese continent throughout the Korean peninsula.…”
mentioning
confidence: 70%
“…The frequency of the ALDH2 variant is 31.9% in the Japanese population 9 . However, among people living in mainland Japan who carry CY genotype JCV, the frequency of the ALDH2 variant is 51.5% 16 . This frequency of the variant allele is much higher than that in the Chinese Guangdong Han (46.7%), and is the highest among Asian populations 9,10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is known as the "dual structure hypothesis" which was formulated by Hanihara Kazurō 埴原和郎 (Hanihara 1991). The Jōmon people were a hunter-gatherer society that occupied the Japanese islands until extensive immigration occurred from the Korean Peninsula, giving rise to the ensuing Yayoi culture that introduced wet rice agriculture, iron tools, and other technologies during the first millennium BCE (Takahashi 2009;Iizuka and Nakahashi 2012;Miyamori et al 2015).…”
Section: Previous Researchmentioning
confidence: 99%
“…DNA viruses commonly establish persisting infections in humans, remaining thus, their genetic material imprinted in the tissues throughout life. These DNAs exhibit phylogeographies resembling those of humans [1], pointing to shared evolutionary and dispersal paths that can, together, add to the understanding of human population history and migrations [2][3][4][5][6][7][8]. In addition, the specific geographical distributions of DNA viruses, in both global [2,9] and local [10][11][12] scales, may provide new insights into the origins of unidentified individuals.…”
Section: Introductionmentioning
confidence: 99%